Remote‐controlled robotic platform ORPHEUS as a new tool for detection of bacteria in the environment. Issue 16 (15th April 2014) - Nejdl, Lukas; Kudr, Jiri; Cihalova, Kristyna; Chudobova, Dagmar; Zurek, Michal; Zalud, Ludek; Kopecny, Lukas; Burian, Frantisek; Ruttkay–Nedecky, Branislav; Krizkova, Sona; Konecna, Marie; Hynek, David; et al.
<x xml:space="preserve">Abstract</x> Remote‐controlled robotic systems are being used for analysis of various types of analytes in hostile environment including those called extraterrestrial. The aim of our study was to develop a remote‐controlled robotic platform (ORPHEUS‐HOPE) for bacterial detection. For the platform ORPHEUS‐HOPE a 3D printed flow chip was designed and created with a culture chamber with volume 600 μL. The flow rate was optimized to 500 μL/min. The chip was tested primarily for detection of 1‐naphthol by differential pulse voltammetry with detection limit (S/N = 3) as 20 nM. Further, the way how to capture bacteria was optimized. To capture bacterial cells (Staphylococcus aureus), maghemite nanoparticles (1 mg/mL) were prepared and modified with collagen, glucose, graphene, gold, hyaluronic acid, and graphene with gold or graphene with glucose (20 mg/mL). The most up to 50% of the bacteria were captured by graphene nanoparticles modified with glucose. The detection limit of the whole assay, which included capturing of bacteria and their detection under remote control operation, was estimated as 30 bacteria per μL.